Estágio supervisionado remoto: implicações para a formação inicial de professores de Ciências e Biologia - SILVA, Marcos Vinicius Marques da (2023)
This research aims to analyze the implications of a Remote Supervised Internship regarding knowledge and professional identity in the initial training of students in the Biological Sciences Teaching Program at the Federal University of Maranhão, São Luís campus. In conducting the research, a qualitative approach was adopted, using instruments and techniques from bibliographic and documentary research, as well as semi-structured interviews and a questionnaire. Data were analyzed using Content Analysis techniques (BARDIN, 2016), which facilitated the construction of the following categories: Organization and development of Remote Supervised Internship; Challenges of Remote Supervised Internship; Mobilization and construction of Teaching Knowledge; and the process of building Professional Identity in the context of Remote Supervised Internship. The study involved twelve (12) interns/graduates who participated in the Remote Supervised Internship in 2020 and 2021. The work is grounded in the contributions of authors such as Pimenta (1999, 2020), Pimenta and Lima (2018), Almeida and Pimenta (2015), Tardif (2014), Dubar (2005), Hall (2000), Marcelo (2009), Guimarães (2004), Souza and Ferreira (2020), Ferraz and Ferreira (2020), Araújo (2021), among others. Additionally, it draws from documents such as Ordinance nº 343/2020, which deals with the replacement of face-to-face classes with digital classes during the COVID-19 pandemic; Ordinance nº 544/2020, which authorized the realization of internships in digital media during the pandemic; Opinion CNE nº 9/2020, which recommended the execution of non-face-to-face activities for practices and internships, especially for teaching and teacher training courses; and Normative Instruction nº 04/2020, which regulates the implementation of obligatory curricular internship activities in the undergraduate courses at the Federal University of Maranhão due to the pandemic caused by the new coronavirus. The results revealed that Emergency Remote Teaching posed unprecedented challenges to the Supervised Internship, requiring the assimilation of complex social demands, particularly with the use of technologies. Among the identified challenges, the restriction of interactions between interns and students stands out, which may have impacted the pedagogical practices developed in this environment. However, the challenges faced prompted interns to seek strategies to overcome them, resulting in the mobilization and construction of different teaching knowledge. In this scenario, the (re)construction of the professional teaching identity occurred through reflection on lived experiences, the mobilization and (re)construction of teaching knowledge, and adaptation to the virtual environment. Despite the unique characteristics of a Remote Supervised Internship, its trajectory proved to be marked by challenges but also valuable learning experiences and overcoming obstacles. Furthermore, it demonstrates itself as a potential formative proposal for the initial training of teachers in post-pandemic scenarios, provided it is carefully reassessed and planned, avoiding the abrupt approach that characterized its implementation during the pandemic. Thus, integrating the Supervised Internship with socially defined objectives for teaching, aligned with a theoretical perspective that conceives it as an instrumental theoretical activity in teaching practice, is crucial to creating opportunities for the construction of knowledge and contributing to the recognition and consolidation of the professional identities of future teachers.